Reporting On Mental Health: This briefing is an account on the launch of the African Report on World Mental Health, and on the Regional Conference on Mental Health Policy, held in Cape Town, 23-25 October 1995. - Pillay, Yogan (PINS-Psychology in Society, 2026)
200 delegates from Africa, Europe and the US attended the first ever Southern African conference on mental health policy. The conference bad a dual purpose: (i) the launch of the African Report on World Mental Health; and (ii) a regional conference on mental health policy. The briefing is not intended to be exhaustive but will focus on the highlights of the conference, notably the keynote addresses by the Western Cape MEC for Health and Welfare and the authors on the Report on World Mental Health. Finally the common themes and strategies of the conference and resolutions adopted will be reported.